Here Is Your Money : Using the Standard Cost Model to Measure Regulatory Compliance Costs in Developing Countries - International Finance Corporation; World Bank (Washington, DC, 2017)
Over the last few years the Standard Cost Model (SCM) has become the regulatory reform tool of choice in European Union (EU) and Organization for Economic Co-operation and Development (OECD) countries for identifying and reducing regulatory compliance costs. SCM provides a relatively simple methodology to measure and communicate businesses' paperwork obligations arising from compliance with governments' regulations. More recently the SCM has also been adapted and applied in a number of developing countries, including Kenya, Zambia, Vietnam, Burkina Faso, and Rwanda. It is still too early days to conclude much on the SCM model's general applicability in developing countries. However as part of a broader reform package the SCM has proven capable of strengthening momentum by providing new insights into regulatory obligations, by quantifying the costs and time associated with information obligations both at aggregate and at a rule-specific level. It has hence proven useful both as a tool to target specific interventions and to monitor the impact of reform. This document provides a number of lessons from the first few years of using SCM in regulatory reforms, with a focus on business licensing, in developing countries. These lessons are not intended to provide a final account on how SCM is to be carried out in developing countries. Along with its dissemination across the globe, SCM has experienced a constant development. This document aims to point out a number of important issues that have been observed and tested during the initial measurements in World Bank client countries to prevent future practitioners from the need to re-invent the wheel.